Physicochemical effects of discrete CO2-SO2 mixtures on injection and storage in a sandstone aquifer. (November 2016) - Waldmann, Svenja; Hofstee, Cor; Koenen, Mariëlle; Loeve, Daniël; Liebscher, Axel; Neele, Filip
Highlights: Storage capacity calculations for CO2 -SO2 mixtures. Porosity changes related to chemical fluid-rock interactions. Impact of chemically induced porosity changes on the overall storage capacity. Identification of potential operation risks during the injection period. Abstract: Geological storage of captured CO2, which typically will contain certain amounts of impurities, in saline aquifers is of potential to reduce greenhouse gas emissions into the atmosphere. The co-injection of the impurity SO2 has an effect on the chemical reactivity of the fluid and solid phases as well as on the physical behaviour of the CO2 plume. To address these influences we assessed the impact of SO2 on the physicochemical behaviour of the CO2 phase by pressure-volume-temperature calculations and geochemical modelling of fluid-rock interactions. As case study, the Ketzin pilot site in Germany was chosen. The results reveal that the presence of SO2 causes a greater porosity decrease compared to pure CO2 during the injection period. Certainly, any textural changes that occur in the vicinity of the injection well are of importance for selecting the right injection strategy and to reduce operational costs. We further assessed the impact of SO2 on the overall CO2 storage capacity at different depth. Particularly, there is a maximum reduction of the storage capacity at low depth, but the general impact of SO2 concentrations <1% is comparatively low. Furthermore, short-term porosity changes that are induced by chemical reactions beyond the dry-out zone will reduce the pore spaces available for storage.